PEMBUATAN DAN UJI MUTU FISIK SEDIAAN DEODORAN SPRAY DARI EKSTRAK PELEPAH SEREH (Cymbopogon nardus L.) - Djajanti, Agust Dwi Djajanti (Jurnal Kesehatan Yamasi Makassar, 2025)
This study aims to determine the preparation and physical quality test of deodorant spray preparation from lemongrass frond extract (Cymbopogon nardus L.) The research method used is laboratory experimental. First the simplisia was extracted by maceration method for 2 x 24 hours using 96% ethanol solvent. The results of the thick extract were made deodorant spray preparations in the form of 4 formulas F1 27%, F2 28% and F3 29% with a deodorant spray base consisting of 96% ethanol, propylenglicol and distilled water. Physical quality tests carried out are organoleptic test, pH test, homogeneity test and dry time test. The results of the organoleptic test F0, F1, F2, F3 have a liquid form, distinctive odor and orange color while for F0 has a liquid form, odorless and clear color. The results of the pH test F0, F1, F2, F3 all preparations have met the requirements with a pH parameter value of 3 - 7.5. The homogeneity test results of all preparations have met the requirements. The dry time test has met the requirements with a drying time of < 5 minutes in the deodorant spray preparation. From the results of the study stated that lemongrass frond extract (Cymbopogon nardus L.) can be made in the form of deodorant spray preparations with a concentration of F0 base, F1 27%, F2 28%, F3 29% have met the quality requirements based on SNI 16-4951-1998.